Type 1 Diabetes Mellitus in Pediatric Patients and Its Impact on Relationships in the Family Environment - Madrigal MA; López M; Sánchez A; Cao MJ; Castro MJ; Jiménez JM (Diabetes, Metabolic Syndrome and Obesity, 2020)
Miguel Angel Madrigal,1,2 María López,1 Alicia Sánchez,2 María José Cao,1 María José Castro,1 José María Jiménez1 1Faculty of Nursing, Universidad de Valladolid, Valladolid, Spain; 2Hospital Clínico Universitario de Valladolid, Valladolid, SpainCorrespondence: María LópezFaculty of Nursing, Universidad de Valladolid, Avda Ramón y Cajal, Nº 7, Valladolid, SpainTel +34 983184056Email maria.lopez.vallecillo@uva.esPurpose: The aim of this study is to assess the impact of type 1 diabetes mellitus on family environment relationships, as well as the management and approach to this disease.Patients and Methods: One hundred one children, 52.47% male and 47.52% female, with an average age of 8.55 ± 4.01 years, diagnosis of type 1 diabetes mellitus. Quantitative cross-sectional descriptive study was conducted using the validated questionnaires “Modified Diabetes Quality of Life” and “Questionnaire for the assessment of psychological impact in parents/guardians of diabetic children”.Results: Most of the children (70.3% versus 29.7%) identified diabetes as unpleasant or not fun. The ≤ 5-year-olds expressed that they felt concerned about the consequences of being diabetic (8.1% by age group), as opposed to the 10-year-olds who did not feel concerned (85.1% by age group), P < 0.001. The family environment was affected in 98.1% (n=99) of the cases.Conclusion: Self-care of type 1 diabetes mellitus in pediatric patients is a complex process that impacts the family environment and their relationship with their peers, especially for children under the age of 5. Fear, concern and insecurity were prevalent feelings in children suffering type 1 diabetes mellitus.Keywords: chronic disease, adaptation, psychological, self-care, child health, psychology